Inhibition by Protein Kinase C Inhibitor of Expression of Leukocyte Function‐associated Antigen‐1 Molecules in Rat Hepatoma AH66F Cells - Nomura, Masaaki (Jpn J Cancer Res, 1997)
To examine the mechanism of inhibition by protein kinase C (PKC) inhibitors of the adhesion of highly malignant hepatoma AH66F cells to the mesentery‐derived mesothelial cell (M‐cell) layer through leukocyte function‐associated antigen‐1 (LFA‐1)/intercellular adhesion molecule‐1, the effects of a PKC inhibitor, NA‐382, on the expression of LFA‐1 molecules in AH66F cells were examined and compared with those in thymocytes from normal rats. NA‐382 inhibited the adhesion of AH66F cells to the M‐cell layer and the expression of LFA‐1 on the membrane of the hepatoma cells after treatment for more than 24 h. It was confirmed that AH66F cells express similar mRNAs for LFA‐1 subunits to those of thymocytes, and their levels were also decreased after treatment with NA‐382. On the other hand, the LFA‐1‐mediated adhesion and the expression of both protein and mRNA for LFA‐1 subunits in thymocytes were not changed by the PKC inhibitor. These results suggest that the expression of LFA‐1 molecules in AH66F cells may be regulated by PKC via quite different mechanisms from those in normal lymphocytes